Curry leaf extract (Murraya Koenigii (L.) Spreng) as a corrosion inhibitor of ASTM A36 steel in H2SO4 solution - Atria Pradityana; Farah Khosfirah; Fairiza Naghda Biwai; Rizaldy Hakim Ash Shidieqqy; Muhammad Lukman Hakim; Pramudya Imawan Santosa; Wan Mohd Norsani Wan Nik (Results in Engineering)
Corrosion is a process of changing the properties of a material due to influence or reaction with the surrounding environment which tends to reduce the quality of material properties. One way to control corrosion is by adding organic, environmentally friendly inhibitors. In this study, curry leaf extract was used as an organic inhibitor, and the test material used was austenitic stainless steel American Standard Testing Materials (ASTM) A36. For the corrosive medium, H2SO4 2 M with concentration variations of 1000 mg/L, 1500 mg/L, 2000 mg/L, 2500 mg/L, and 3000 mg/L. The types of tests carried out in this study were weight loss, potentiodynamic polarization, and scanning electron microscope (SEM). The test results showed a decreasing in the corrosion rate of ASTM A36 steel when inhibitors were added. In the weight loss test, the value of the corrosion rate without an inhibitor was 128.083 mmpy while with an inhibitor it was 25.542 mmpy and the inhibition efficiency was 80.058 %. In the Potentiodynamic Polarization test, the resulting efficiency was 76.759 %. Other supporting tests (SEM) show the addition of inhibitors produces a thin protective layer on the surface of ASTM A36 steel. The results showed that curry leaf extract is a good corrosion inhibitor.